A nanocarrier system that potentiates the effect of miconazole within different interkingdom biofilms - Arias, Laís Salomão [UNESP]; Brown, Jason L; Butcher, Mark C; Delaney, Christopher; Monteiro, Douglas Roberto [UNESP]; Ramage, Gordon (Taylor & Francis, 2020)
Background: Novel and new therapeutic strategies capable of enhancing the efficacy of existing antimicrobials is an attractive proposition to meet the needs of society. Objective: This study aimed to evaluate the potentiating effect of a miconazole (MCZ) nanocarrier system, incorporated with iron oxide nanoparticles (IONPs) and chitosan (CS) (IONPs-CS-MCZ). This was tested on three representative complex interkingdom oral biofilm models (caries, denture and gingivitis). Materials and methods: The planktonic and sessile minimum inhibitory concentrations (MICs) of IONPs-CS-MCZ against different Candida albicans strains were determined, as well as against all represented bacterial species that formed within the three biofilm models. Biofilms were treated for 24 hours with the IONPs-CS nanocarrier system containing MCZ at 64 mg/L, and characterized using a range of bioassays for quantitative and qualitative assessment. Results: MIC results generally showed that IONPs-CS-MCZ was more effective than MCZ alone. IONPs-CS-MCZ also promoted reductions in the number of CFUs, biomass and metabolic activity of the representative biofilms, as well as altering biofilm ultrastructure when compared to untreated biofilms. IONPs-CS-MCZ affected the composition and reduced the CFEs for most of the microorganisms present in the three evaluated biofilms. In particular, the proportion of streptococci in the biofilm composition were reduced in all three models, whilst Fusobacterium spp. percentage reduced in the gingivitis and caries models, respectively. Conclusion: In conclusion, the IONPs-CS-MCZ nanocarrier was efficient against three in vitro models of pathogenic oral biofilms, showing potential to possibly interfere in the synergistic interactions among fungal and bacterial cells within polymicrobial consortia.
Keywords: antimicrobials; Biofilms; interkingdom; miconazole; nanocarriers